Radiation Use Efficiency of Maize (Zea mays L.) on Different Varieties and Intercropping with Mungbean in the Rainy Season - Sija, Patta; Sugito, Yogi; Suryanto, Agus; Hariyono, Didik (AGRIVITA, Journal of Agricultural Science, 2020)
The variety selection and intercropping system are closely related to canopy architecture which determines the capability of maize crops to intercept and absorb the intensity of solar radiation. The research to increase radiation use efficiency (RUE) of maize based on varietal selection and intercropping with mungbean related to canopy characteristics. The experiment was conducted during the rainy season, from September 2016 to January 2017, in Gowa Regency, South Sulawesi. A factorial randomized block experiment with three replicates was designed the fasilitate the combination of two factor. The first factor was three maize varieties, i.e. Bisi 18, Lamuru, and local variety and the second factors dealt with intercropping systems, i.e. intercropping of maize varity with one, two, three, and four lines of mungbean, and maize monoculture. The results showed that there were interactions between varieties and intercropping to RUE of maize. The RUE of all maize varieties intercropped with mungbean was higher compared to the maize monoculture. The RUE of Bisi 18 intercropped with mungbean was higher than Lamuru and local varieties with the values of 9.53%, 8.80%, and 6.43% respectively. Bisi 18 that has vertical leaf character were more efficient in utilizing solar radiation when intercropped with denser mungbean populations.